2016
DOI: 10.4314/njp.v43i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable birth injury complicated with limb gangrene: a reflection of an in-efficient health system

Abstract: Gangrene of the lower extremities in neonates is a rare event except in traumatic cases. When risk factors for trauma to the limb of the newborn exist, it is important to prevent such injuries and when they are inevitable, appropriate management of injuries should further prevent complications such as limb gangrene. This report describes a newborn whose birth was poorly managed and thereafter sustained traumatic unilateral lower limb gangrene from the management of femoral fracture at a traditional bone settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The study revealed that the risk of death due to birth injury was much higher compared to infection. The finding was coherent with studies conducted in India [ 75 ] and Nigeria [ 76 ]. This might be partly related to cranial injuries of the neonate, which result in hemorrhage, increasing the risk of encountering high intracranial pressure, coagulopathy, and hypovolemic shock [ 77 ].…”
Section: Discussionsupporting
confidence: 90%
“…The study revealed that the risk of death due to birth injury was much higher compared to infection. The finding was coherent with studies conducted in India [ 75 ] and Nigeria [ 76 ]. This might be partly related to cranial injuries of the neonate, which result in hemorrhage, increasing the risk of encountering high intracranial pressure, coagulopathy, and hypovolemic shock [ 77 ].…”
Section: Discussionsupporting
confidence: 90%